Successful Vaginal Delivery of Naturally Conceived Dicavitary Twin in Didelphys Uterus: A Rare Reported Case - Houda Nasser Al Yaqoubi; Nishat Fatema (Hindawi Limited, 2017)
Didelphys uterus, or double uterus, is an embryological developmental malformation of the müllerian ducts with the incidence of approximately 8.3% of all müllerian duct abnormalities (MDAs). Didelphys uterus accompanying dicavitary twin gestation is encountered as a very rare entity with overall incidence of about 1 in 1,000,000. We report a rare case of didelphys uterus, diagnosed since her first pregnancy, and during her fourth pregnancy she conceived dicavitary twin naturally without any infertility treatment. Though, the pregnancy course was complicated by preterm labour at 34-week gestation and she delivered simultaneously both fetuses with the cephalic presentation by spontaneous vaginal delivery with good maternal and neonatal outcomes.